2020
DOI: 10.1007/s40037-020-00641-w
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes SPECIAL (Students Providing Education on Chronic Illness and Lifestyle): a novel preclinical medical student elective

Abstract: Background Traditional medical student curricula limit substantial clinical experiences until the third and fourth years of medical school. This delay in valuable experiences hinders the ability of some medical students to choose a specialty to pursue, delays the formation of meaningful longitudinal mentorship relationships, and limits the development of important clinical acumen. Furthermore, the use of medical students in preclinical years may help to improve patient care and outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Meyers et al evaluated the impact on patient outcomes of a new elective, SPECIAL (Students Providing Education on Chronic Illness and Lifestyle) that was introduced to first year medical students in United States. Patients reported positive experience and most of them had a reduction in their glycated hemoglobin levels, which supports the importance of early introduction to clinical exposure in medical education [ 41 ].…”
Section: Discussionmentioning
confidence: 76%
“…Meyers et al evaluated the impact on patient outcomes of a new elective, SPECIAL (Students Providing Education on Chronic Illness and Lifestyle) that was introduced to first year medical students in United States. Patients reported positive experience and most of them had a reduction in their glycated hemoglobin levels, which supports the importance of early introduction to clinical exposure in medical education [ 41 ].…”
Section: Discussionmentioning
confidence: 76%
“…14 To address this knowledge gap, 1 medical school implemented a novel preclinical elective in which a medical student was paired with an attending endocrinologist for patient care during 1 semester; student performance was assessed by comparing patients' serum hemoglobin A1C levels before and after the student's involvement. 15 The study reported significant improvements in patients' glycemic control and attributed these improvements to the student's involvement in practical diabetes management. 15 In line with this model, identifying endocrine mentors for students early on during the preclinical years may help improve students' understanding of core clinical concepts and potentially spur interest in endocrinology.…”
Section: Discussionmentioning
confidence: 99%
“…15 The study reported significant improvements in patients' glycemic control and attributed these improvements to the student's involvement in practical diabetes management. 15 In line with this model, identifying endocrine mentors for students early on during the preclinical years may help improve students' understanding of core clinical concepts and potentially spur interest in endocrinology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation